Shaping the Future of Politics: Transforming Legislative Candidate Campaigns Through Social Media - Mardhiah, Ainol; Puspasari, Cindenia; Husniati, Ade Muana; Arinanda, Arinanda (FISIP Universitas Malikussaleh, 2024)
One of the changes in political communication strategies is caused by technological changes. Social media is one of the political communication channels for women legislative candidates in conducting their political campaigns in the 2024 legislative elections. This research aims to reveal how the use of social media in the campaign strategy of female legislative candidates in the digital era? What are the benefits obtained by legislative candidates who effectively use social media in their political campaigns. The approach used in this research is descriptive qualitative while the natural informants of this research are female legislative candidates from local SIRA Party, Democratic Party and PDI-P Party who are in electoral district 1 (Dapil 1) for Aceh Besar, Banda Aceh and Sabang. The results of the study found that the use of social media in campaign strategies for female legislative candidates in the digital era, that social media is a medium for developing the image and branding of female candidates, the presence of social media makes it easy for candidates to communicate directly with voters, become a channel for discussing matters related to gender issues and become a means to gain women's support. The advantages felt by female legislative candidates in using social media for their political campaigns are; social media's ability to reach a wide audience, the ability to interact with the public, and the ability to communicate with the public.